Temperature dependence of piezo- and ferroelectricity in ultrathin P(VDF–TrFE) films. Issue 51 (16th August 2018) - Qian, Jun; Jiang, Sai; Wang, Qijing; Yang, Chengdong; Duan, Yiwei; Wang, Hengyuan; Guo, Jianhang; Shi, Yi; Li, Yun
Abstract : The electromechanical activity and polarization nature of the quasi-2D ultrathin polycrystalline P(VDF–TrFE) were clearly demonstrated, revealing a promising avenue for nano-electro-mechanical and nano-ferroelectric applications using ultrathin P(VDF–TrFE) films. Abstract : The polymer poly(vinylidene fluoride- co -trifluoroethylene) (P(VDF–TrFE)) is highly desirable for piezoelectric and ferroelectric functional applications owing to its considerable electromechanical activity and reliable electrical polarization. However, a clear understanding of the effect of the thermal annealing on the electromechanical behavior and polarization nature of ultrathin crystalline P(VDF–TrFE) films is severely lacking. Here we report the thermally induced structural reorganization, and piezo- and ferroelectric features in the ultrathin P(VDF–TrFE) films. On applying a 40 °C annealing treatment, the polarization-patterned electrostrictive strain reaches the highest value of ∼53.7 pm. Besides, the ultrathin film exhibits a highly ordered antiparallel dipole alignment, the highest local piezoelectric activity, and an improved polarization relaxation time. The optimum film properties are achieved owing to a high degree of polymer chains oriented parallel to the substrate plane. Our results can reveal a promising avenue for nano-electro-mechanical and nano-ferroelectric electronic applications using ultrathin P(VDF–TrFE) films.